COVID-19 in Children With Liver Disease - Di Giorgio, Angelo; Hartleif, Steffen; Warner, Suzan; Kelly, Deirdre (Frontiers in Pediatrics, 2021)
Background: The global pandemic caused by novel Coronavirus SARS-CoV-2 disease (COVID-19) is a major threat to the general population and for patients with pre-existing chronic conditions. We report data concerning SARS-COV-2 infection in children with chronic liver disease (CLD). Methods: A literature review using the online database PubMed was performed to summarise available findings on the association between pre-existing liver disease and COVID-19 infection in children. Results: Children with COVID-19 have preserved effector and immunosuppressive components resulting in a milder disease compared to adults. The most common hepatic manifestation is an elevation of hepatic transaminases. Liver damage may be directly caused by viral infection of liver cells, by medications or by the chronic hypoxia seen in COVID-19 patients. A multicentre study reported that the majority of children with a CLD remained healthy during the outbreak. Similarly, studies reported that children on immunosuppressive treatment, including patients with autoimmune liver disease (AILD) and liver transplantation (LT), maintained good health during the outbreak without experiencing major complications even if infected with COVID-19. Conclusion: COVID-19-related liver injury presents with a mild elevation of transaminases, although its clinical significance is unclear. Children with CLD, including those with AILD and post LT, do not have an increased risk for severe disease course of SARS-CoV2 infection with little or no liver dysfunction. These data highlight the necessity to ensure normal standards of care while adhering to national Covid-19 guidelines, and particularly to maintain immunosuppressive medication to prevent relapse or rejection. Further research is required to evaluate the differences in clinical course between immunosuppressed adults and children and in particular whether asymptomatic infection is a concern.